2008
DOI: 10.1063/1.2804420
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of liquid ammonia: A sequential molecular dynamics/quantum mechanics approach

Abstract: Electronic structures of c-plane and a-plane AlN/ZnO heterointerfaces determined by synchrotron radiation photoemission spectroscopy Appl. Phys. Lett. 97, 252111 (2010) Theoretical predictions of trends in spectroscopic properties of gold containing dimers of the 6p and 7p elements and their adsorption on gold J. Chem. Phys. 133, 104304 (2010) Additional information on J. Chem. Phys. The electronic properties of liquid ammonia are investigated by a sequential molecular dynamics/ quantum mechanics approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 57 publications
2
35
0
Order By: Relevance
“…As representative values we assume E F À E C ¼ 2.5 eV for LSMO and E F À E C ¼ 0.5 eV for graphene. Electronic properties of ammonia are characterized by the energy gap between the LUMO and HOMO states of about 10 eV 35 . For the Fermi energy lying in the middle of the gap, the effective potential barrier produced by ammonia is U A ¼ 5 eV.…”
Section: Methodsmentioning
confidence: 99%
“…As representative values we assume E F À E C ¼ 2.5 eV for LSMO and E F À E C ¼ 0.5 eV for graphene. Electronic properties of ammonia are characterized by the energy gap between the LUMO and HOMO states of about 10 eV 35 . For the Fermi energy lying in the middle of the gap, the effective potential barrier produced by ammonia is U A ¼ 5 eV.…”
Section: Methodsmentioning
confidence: 99%
“…This model is referred to as Sþ29Wþ225PC and involves super-molecular structures with as much as 374 electrons. Previous experiences [42] have indicated that the electrostatic embedding has an stabilizing effect on the dependence of the results with the number of explicit solvent molecules included. Thus, we expect that using solvent molecules well beyond the first solvation shell will have little effect on the transition energies reported here.…”
Section: Computational Detailsmentioning
confidence: 98%
“…In fact, Almeida et al [28], considering embedding clusters of different size, calculate dipole moment values equal to 2.00 D, 2.01 D and 2.05 D for the NH 3 monomer in the dimer, the pentamer and liquid ammonia, respectively. The same values have been used in the present study, while the corresponding values for the trimer and the tetramer have been interpolated from 2.00 D and 2.01 D. The increase of the dipole moment going from gas phase to liquid was also evidenced for water from a combined experimental and theoretical study of small clusters (up to six monomers) [36] and it was applied successfully to study both, some small clusters and liquid water [30].…”
Section: The Nh 3 -Nh 3 Interactionmentioning
confidence: 99%
“…Due to both the mentioned separability between electrostatic and nonelectrostatic contributions and the flexibility of the ILJ function, V nel can be combined with different descriptions of the electrostatic contribution. In the present investigation we use a simple 4-site for NH 3 , whose charges are selected taking into account the increase of about a 27% of the monomer dipole moment (μ) in liquid environment in comparison with the gas phase value [28].…”
Section: Introductionmentioning
confidence: 99%